1986
DOI: 10.1007/bf00027137
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of tobacco mosaic virus replicative structures synthesized in vitro

Abstract: The RNA structures synthesized in vitro by a crude enzyme complex from tobacco mosaic virus (TMV)-infected leaves have been analyzed; the major viral-specific products were similar to TMV-replicative form (RF) and-replicative intermediate (RI) in electrophoretic behavior and ribonuclease sensitivity. Synthesis of these RF-like and RI-like structures neither required nor responded to added viral RNA, but did require all four ribonucleotide triphosphates. Enriched radiolabeled RF-like and RI-like RNA fractions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…We suggest that the structures may be similar to those described in the earlier studies. This proposal is consistent with previous observations that the replication complexes of TMV copurify with membrane extracts from infected cells (Watanabe and Okada, 1986;Young and Zaitlin, 1986;Young et al, 1987;Restrepo et al, 1990;Osman and Buck, 1996). Recent experiments in our laboratory have confirmed that both the MP and replicase are associated with the ER isolated from infected leaf tissues (C. Reichel and R.N.…”
supporting
confidence: 82%
“…We suggest that the structures may be similar to those described in the earlier studies. This proposal is consistent with previous observations that the replication complexes of TMV copurify with membrane extracts from infected cells (Watanabe and Okada, 1986;Young and Zaitlin, 1986;Young et al, 1987;Restrepo et al, 1990;Osman and Buck, 1996). Recent experiments in our laboratory have confirmed that both the MP and replicase are associated with the ER isolated from infected leaf tissues (C. Reichel and R.N.…”
supporting
confidence: 82%
“…This conclusion is supported by the observation that CPMV RF cannot infect cowpea plants unless it is first denatured (Shanks et aL, 1985). Earlier suggestions for functions of RF are that it represents a functional replication intermediate (Koch & Koch, 1985), an isolation artefact (Hall et al, 1982;Richards et al, 1984) or a 'dead-end' molecule arising either in non-optimally replicating in vitro systems (Chu & Westaway, 1987;Hall et al, 1982;Jaspars et aL, 1985;Kuhn & Wimmer, 1987;Morrow et al, 1985;Mouch6s et al, 1974;Watanabe & Okada, 1986;Young & Zaitlin, 1986) or accumulating in vivo at the end of the infection cycle (Koch & Koch, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Molecules resembling RF and RI have also been detected following TMV RNA synthesis in vitro using polymerase preparations from infected plants or protoplasts Young & Zaitlin 1986;Osman & Buck 1996). In RI RNA, the number of positive strands on average exceeds that of the negative strands (Aoki & Takebe 1975) and the structure of an RI molecule has been interpreted as a single negative strand to which are attached several positive strands of di¡erent lengths (¢gure 1).…”
mentioning
confidence: 99%
“…Similarly RI RNA could exist in vivo in a predominantly single-stranded structure, as for bacteriophage Q b (¢gure 1a), or in either of two possible double-stranded structures with singlestranded tails, one involving semi-conservative strand displacement (¢gure 1b) and the other involving a conservative mechanism in which the duplex RNA is only transiently unwound at the growing end of the nascent strands (¢gure 1c). During synthesis of TMV RF in in vitro systems with labelled NTP substrates, most of the label is found in the positive strand of the RF (Young & Zaitlin 1986;Osman & Buck 1996). This is inconsistent with a conservative mechanism (¢gure 1c), but is consistent with either a semi-conservative strand-displacement mechanism (¢gure 1b) or formation of RF by annealing of free (+) and (À) strands.…”
mentioning
confidence: 99%